Russian Historiography of Regional Policy of the United Germany (since 1990) - I. D. Popov (Научный диалог)
The Russian historiography of the FRG regional policy after the unification of Germany is analyzed. Historical, political, legal, economic, cultural and geographical scientific works devoted to the relationship between the centre and the regions of Germany are considered. It is concluded that most of works are concentrated around the phenomenon of German federalism, inter-budgetary relations and problem of integration of the former lands of the GDR. The author covers discussions on the sustainability and effectiveness of cooperative federalism, problems of inter-budgetary relations, the prospects of a competitive model of federalism as a result of Federal reforms of the 21st century, the impact of regional imbalances on domestic policy, the possibility of unification of the Federal lands and their adaptation to the challenges of European integration. The state of study of the development of individual regions and local government of Germany is presented. Estimates of land elections and their influence on regional policy are given. Despite the recognition of the significant influence of the länder and municipalities on the domestic and foreign policy of the United Germany by many scholars, their position as political actors is usually either given in an overview or appears as an illustrative material to the general pattern. In conclusion, the main gaps in the study of the regional policy of modern Germany are listed, the elimination of which will help to get closer to a holistic view of the political significance of the land and municipal levels of government.